Aluminum alloy brazing sheet, manufacturing method thereof, aluminum alloy sheet and heat exchanger

By using aluminum alloy brazed sheets, combined with specific element composition and manufacturing processes, the problem of difficult to destroy the oxidation coating in the non-active gas atmosphere in the prior art is solved, and excellent brazing performance is achieved and cost reduction.

CN114734161BActive Publication Date: 2025-02-18UACJ CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202210005964.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2015-10-16
Filing Date
2016-10-13
Publication Date
2025-02-18
Estimated Expiration
2036-10-13

AI Technical Summary

Technical Problem

The existing brazing technology is difficult to effectively destroy the oxidation coating in an inactive gas atmosphere without using flux, resulting in uneven welding feet, and requires expensive vacuum heating equipment and high maintenance costs.

Method used

Aluminum alloy brazed sheet is made of aluminum or aluminum alloy core material and clad aluminum alloy brazing material. The brazing material contains 4.0 to 13.0 mass% Si, and the core material and brazing material contain Mg, Li, Elements such as Be, Ca, Ce, La, Y and Zr are formed by hot and cold rolling, intermediate annealing or final annealing to form excellent brazing properties.

Benefits of technology

In an inactive gas atmosphere without flux, excellent brazing performance is achieved. The volume change rate of the oxidized coating formed on the surface is below 0.99. The new surface of the brazing material is effectively exposed, which improves the uniformity and strength of welding and reduces the Equipment and maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003456741300000151
    Figure BDA0003456741300000151
  • Figure BDA0003456741300000161
    Figure BDA0003456741300000161
  • Figure BDA0003456741300000171
    Figure BDA0003456741300000171
Patent Text Reader

Abstract

An aluminum alloy brazing sheet having excellent brazing properties in brazing in an inert gas atmosphere without using a flux, a method for manufacturing the same, an aluminum alloy sheet, and a heat exchanger are provided. An aluminum alloy brazing sheet is characterized in that it is an aluminum alloy brazing sheet for brazing in an inert gas atmosphere without using a flux, and is formed of a core material of aluminum or an aluminum alloy, and a brazing filler metal of an aluminum alloy containing 4.0 to 13.0 mass % Si clad on one or both surfaces of the core material, and one or both of the core material and the brazing filler metal contain any one or two or more of X atoms (X is Mg, Li, Be, Ca, Ce, La, Y, and Zr), and the aluminum alloy brazing sheet is a brazing sheet that forms oxide particles containing X atoms on the surface of the sheet by brazing heating, the volume change rate of the oxide film before brazing heating being 0.99 or less.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present application is a divisional application of an application filed on October 13, 2016, with application number 201680060575.X, and invention name Aluminum alloy brazing sheet, manufacturing method thereof, aluminum alloy sheet and heat exchanger. Technical Field

[0002] The present invention relates to an aluminum alloy brazing sheet used for brazing of aluminum or aluminum alloy in an inert gas atmosphere without using a flux, a method for producing the same, and an aluminum alloy sheet and a heat exchanger obtained by performing brazing heating using the same. Background Art

[0003] Brazing is widely used as a method for joining aluminum products with many fine joints, such as aluminum heat exchangers and mechanical parts. In order to braze aluminum or aluminum alloys, the oxide film covering the surface must be destroyed, the molten brazing material must be exposed, and the base material or the similarly molten brazing material must be wetted. In order to destroy the oxide film, there are two methods: a method using a flux in a nitrogen furnace and a method not using a flux in a vacuum heating furnace, both of which have been put into practical use.

[0004] When utilizing the method of using flux in a nitrogen furnace, the flux reacts with the oxide film and destroys the oxide film during brazing heating. However, there is a problem of increased cost of the flux and the cost of the process of applying the flux. In addition, when the flux is applied unevenly, there is a risk of poor brazing. On the other hand, the method of not using flux in a vacuum heating furnace uses a brazing material formed of an Al-Si-Mg alloy, and the Mg in the brazing material evaporates by heating in a vacuum, destroying the oxide film on the surface of the material. However, there is a disadvantage of requiring expensive vacuum heating equipment. In addition, since the evaporated Mg adheres to the furnace, there is a problem of high maintenance costs for removing the attached Mg. Therefore, the demand for joining without using flux in a nitrogen furnace has increased.

[0005] In order to respond to such a demand, for example, Patent Document 1 proposes that surface bonding can be achieved by including Mg in the brazing filler metal. In addition, Patent Document 2 proposes that a weld foot can be formed with a simple fin / tube joint by including Mg in the core material and diffusing Mg into the brazing filler metal during brazing heating. However, when using these techniques, in a real joint with a gap, a sufficient weld foot cannot be formed without applying a flux. That is, for these techniques, after the oxide film is dispersed into particles by Mg, the new surface of the molten brazing filler metal is exposed due to the thermal expansion difference between the molten brazing filler metal and the oxide film or the flow of the solder, resulting in wetting. Therefore, when using these techniques, a deformed weld foot is formed in a real joint. In order to form a uniform weld foot even in a real joint, the new surface of the molten brazing filler metal needs to be exposed on the entire surface of the brazing filler metal.

[0006] In addition, Patent Document 1 proposes that it is effective to suppress the thickness of the MgO film on the oxide film before brazing heating. However, in Patent Document 1, in which the brazing material contains 0.1% or more of Mg, in actual joints, a MgO-based film is partially formed during brazing heating, which hinders the formation of the weld leg and thus causes weld leg discontinuity. On the other hand, Patent Document 3 proposes a method in which a pickling treatment is performed before brazing heating in a material in which the brazing material contains 0.05% or more of Mg, thereby removing the MgO-based film and brazing without flux. However, similar to Patent Document 1, the formation of the MgO-based film during brazing heating cannot be fully suppressed.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2013-215797

[0010] Patent Document 2: Japanese Patent Application Publication No. 2004-358519

[0011] Patent Document 3: Japanese Patent Application Laid-Open No. 11-285817 Summary of the invention

[0012] Problem that the invention aims to solve

[0013] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide an aluminum alloy brazing sheet having excellent brazing properties in brazing in an inert gas atmosphere without using a flux, and a method for producing the same.

[0014] Solutions for solving problems

[0015] The above-mentioned object is achieved by the present invention described below.

[0016] That is, the present invention (1) provides an aluminum alloy brazing sheet, characterized in that it is an aluminum alloy brazing sheet used for brazing in an inert gas atmosphere without using a flux,

[0017] It is composed of a core material of aluminum or aluminum alloy and a brazing filler metal of an aluminum alloy containing 4.0 to 13.0 mass % of Si clad on one or both sides of the core material.

[0018] Either or both of the core material and the brazing filler metal contain any one or two or more of X atoms (X is Mg, Li, Be, Ca, Ce, La, Y and Zr),

[0019] When only the core material contains X atoms, the content of each X atom in the core material is 0.01 to 2.0 mass %.

[0020] When the brazing material contains only X atoms, the content of each X atom in the brazing material is 0.001 to 0.03 mass %.

[0021] When both the core material and the brazing filler metal contain X atoms, the content of each X atom in the core material is 0.01 to 2.0 mass %, and the content of each X atom in the brazing filler metal is 0.001 to 0.03 mass %,

[0022] The aluminum alloy brazing sheet is a brazing sheet having oxide particles containing X atoms whose volume change rate relative to the oxide film before brazing heating is 0.99 or less formed on the surface thereof by brazing heating.

[0023] In addition, the present invention (2) provides a method for manufacturing an aluminum alloy brazing sheet, characterized in that it is a method for manufacturing an aluminum alloy brazing sheet in which a core material and a brazing filler metal are overlapped, or a core material, a brazing filler metal and a sacrificial anode material are overlapped, and then hot and cold rolling is performed to obtain a brazing sheet, and it is a method for manufacturing an aluminum alloy brazing sheet in which intermediate annealing or final annealing is performed in the manufacturing process.

[0024] The core material is formed of aluminum or an aluminum alloy, and the brazing filler metal is formed of an aluminum alloy containing 4.0 to 13.0 mass % of Si.

[0025] Either or both of the core material and the brazing filler metal contain any one or two or more of X atoms (X is Mg, Li, Be, Ca, Ce, La, Y and Zr),

[0026] When only the core material contains X atoms, the content of each X atom in the core material is 0.01 to 2.0 mass %.

[0027] When the brazing material contains only X atoms, the content of each X atom in the brazing material is 0.001 to 0.03 mass %.

[0028] When both the core material and the brazing filler metal contain X atoms, the content of each X atom in the core material is 0.01 to 2.0 mass %, and the content of each X atom in the brazing filler metal is 0.001 to 0.03 mass %,

[0029] In the intermediate annealing or final annealing performed in the manufacturing process, the intermediate annealing or final annealing is performed by heating at 250 to 450° C. in an atmosphere controlled to have an oxygen concentration of 1000 ppm or less and a dew point of −20° C. or less, and then taking out of the furnace at 250° C. or less.

[0030] In addition, the present invention (3) provides an aluminum alloy sheet, characterized in that it is an aluminum alloy sheet obtained by brazing and heating the aluminum alloy brazing sheet of (1) in an inert gas atmosphere without using a flux,

[0031] Oxide particles containing X atoms having a volume change rate of 0.99 or less relative to that of an oxide film of the aluminum alloy brazing sheet before brazing heating are formed on the surface of the aluminum alloy sheet.

[0032] In addition, the present invention (4) provides a heat exchanger characterized in that it is a heat exchanger obtained by using the aluminum alloy brazing sheet (1) and performing brazing heating in an inert gas atmosphere without using a flux,

[0033] In the heat exchanger, oxide particles containing X atoms having a volume change rate of 0.99 or less relative to that of the oxide film of the aluminum alloy brazing sheet before brazing heating are formed on the surface of the aluminum alloy sheet after brazing heating.

[0034] Effects of the Invention

[0035] According to the present invention, it is possible to provide an aluminum alloy brazing sheet having excellent brazing properties in brazing in an inert gas atmosphere without using a flux, and a method for producing the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a figure which shows the assembly of the cup test piece in Example and Comparative Example.

[0037] Figure 2 This is a SEM photograph of the surface of the test material after brazing heating in Test No. 30 of the Example. DETAILED DESCRIPTION

[0038] The aluminum alloy brazing sheet of the present invention is characterized in that it is an aluminum alloy brazing sheet used for brazing in an inert gas atmosphere without using a flux.

[0039] It is composed of a core material of aluminum or aluminum alloy and a brazing filler metal of an aluminum alloy containing 4.0 to 13.0 mass % of Si clad on one or both sides of the core material.

[0040] Either or both of the core material and the brazing filler metal contain any one or two or more of X atoms (X is Mg, Li, Be, Ca, Ce, La, Y and Zr),

[0041] When only the core material contains X atoms, the content of each X atom in the core material is 0.01 to 2.0 mass %.

[0042] When the brazing material contains only X atoms, the content of each X atom in the brazing material is 0.001 to 0.03 mass %.

[0043] When both the core material and the brazing filler metal contain X atoms, the content of each X atom in the core material is 0.01 to 2.0 mass %, and the content of each X atom in the brazing filler metal is 0.001 to 0.03 mass %,

[0044] The aluminum alloy brazing sheet is a brazing sheet having oxide particles containing X atoms whose volume change rate relative to the oxide film before brazing heating is 0.99 or less formed on the surface thereof by brazing heating.

[0045] The aluminum alloy brazing sheet of the present invention is an aluminum alloy brazing sheet used for brazing: brazing of aluminum or an aluminum alloy is performed by performing brazing heating in an inert gas atmosphere without using a flux.

[0046] The aluminum alloy brazing sheet of the present invention is formed of a core material and a brazing filler metal. The core material is formed of aluminum or an aluminum alloy, and the brazing filler metal is formed of an aluminum alloy clad on one or both surfaces of the core material.

[0047] In the aluminum alloy brazing sheet of the present invention, either or both of the core material and the brazing filler metal contain any one or two or more of the X atoms (X is Mg, Li, Be, Ca, Ce, La, Y, and Zr). That is, the aluminum alloy brazing sheet of the present invention has (A) a form in which only the core material contains the X atoms, (B) a form in which only the brazing filler metal contains the X atoms, and (C) a form in which both the core material and the brazing filler metal contain the X atoms. It should be noted that in the present invention, the X atom is a general term for Mg, Li, Be, Ca, Ce, La, Y, and Zr, and refers to one or more of these atoms.

[0048] The X atoms destroy the oxide film formed on the surface of the brazing material during the brazing heating, effectively exposing the new surface of the molten brazing material. In addition, the oxide formation energy of the X atoms is smaller than that of Al, so during the brazing heating, the oxide film with Al as the main component is reduced to form a granular oxide containing the X atoms.

[0049] The aluminum alloy brazing sheet of the present invention is an aluminum alloy brazing sheet in which oxide particles containing X atoms are formed on the surface of the brazing material by brazing heating in an inert gas atmosphere without using a flux, and the volume change rate of the oxide film formed on the surface of the brazing material before brazing is 0.99 or less, preferably 0.70 to 0.97, and particularly preferably 0.70 to 0.95. During the brazing heating in an inert gas atmosphere without using a flux, the oxide containing X atoms in the form of particles having a volume change rate within the above range relative to the oxide film formed on the surface of the brazing material before brazing is formed, so that the newly formed surface of the brazing material is effectively exposed during the brazing heating, and thus the aluminum alloy brazing sheet has excellent brazing properties. On the other hand, during brazing heating in an inactive gas atmosphere without using a flux, if the volume change rate of the oxide formed on the surface of the brazing material relative to the oxide film formed on the surface of the brazing material before brazing is greater than the above range, the new surface of the brazing material is difficult to expose during brazing heating. It should be noted that in the present invention, the volume change rate of the oxide particles containing X atoms formed by brazing heating refers to the volume change rate of the oxide film formed on the surface of the brazing material before brazing, which is the value obtained using the formula "the volume of each oxygen atom of the oxide particles containing X atoms formed by brazing heating / the volume of each oxygen atom of the oxide film formed on the surface of the brazing material before brazing". In the formula, the volume of each oxygen atom is calculated by dividing the molecular weight of the oxide by the density of the oxide.

[0050] X atoms (X is Mg, Li, Be, Ce, La, Y, and Zr) are atoms that are effective for exposing the new surface of the brazing material during brazing heating in an inert gas atmosphere without a flux, because they not only have a lower oxide formation free energy than Al and can reduce the oxide film, but also can form an oxide with a volume change rate of 0.99 or less. For example, the volume change rate of MgO is 0.994, while the volume change rate of MgAl2O4 is 0.863, which is less than 0.99. On the other hand, although Ba, Th, Nd, etc. are atoms that have a lower oxide formation free energy than Al, there are no oxides with a volume change rate of 0.99 or less, and therefore they are not effective atoms. For example, the volume change rates of BaO and BaAl2O4, which are oxides containing Ba, are 2.366 and 1.377, respectively, and there is no Ba oxide with a volume change rate of 0.99 or less. As oxides that form oxides with a free energy of oxide formation lower than that of Al and a volume change rate of less than 0.99, there are LiAl5O8 (volume change rate = 0.822), BeAl2O4 (volume change rate = 0.763), CaAl 12 O 19(volume change rate = 0.967), CeAlO3 (volume change rate = 0.957), LaAlO3 (volume change rate = 0.965), ZrO2 (volume change rate = 0.947), Y3Al5O 12 (Volume change rate = 0.960) etc.

[0051] In the aluminum alloy brazing sheet of the present invention, in the case of (A) only the core material contains X atoms, the content of each X atom in the core material is 0.01 to 2.0 mass%, preferably 0.1 to 1.8 mass%, in the case of (B) only the brazing material contains X atoms, the content of each X atom in the brazing material is 0.001 to 0.03 mass%, preferably 0.005 to 0.025 mass%, and in the case of (C) both the core material and the brazing material contain X atoms, the content of each X atom in the core material is 0.01 to 2.0 mass%, preferably 0.1 to 1.8 mass%, and the content of each X atom in the brazing material is 0.001 to 0.03 mass%, preferably 0.005 to 0.025 mass%. If the content of each X atom in the brazing material is less than the above range, the effect of destroying the oxide film by the X atoms is insufficient, and if it exceeds the above range, the X atoms are oxidized during brazing heating to form oxides having a volume change rate exceeding 0.99. In addition, if the content of X atoms in the core material is less than the above range, the diffusion of X atoms into the brazing material is insufficient, so the effect of destroying the oxide film is insufficient. In addition, if it exceeds the above range, the melting point of the core material is excessively reduced, so the core material is partially melted during brazing heating, the core material is deformed, and the core material is corroded by the molten brazing material, and the brazing adhesion and corrosion resistance are reduced. It should be noted that the content of each X atom in the core material and the brazing material is the content of the one X atom when the core material or the brazing material contains only one X atom, and is the content of each of the two or more X atoms when the core material or the brazing material contains two or more X atoms.

[0052] The core material may be made of aluminum (containing inevitable impurities is allowed), or may be made of an aluminum alloy containing predetermined atoms with the balance being aluminum and inevitable impurities.

[0053] The aluminum alloy of the core material is an aluminum alloy containing: X atoms having a content of 2.0 mass % or less of each X atom; and any one or more of 1.8 mass % or less of Mn, 1.2 mass % or less of Si, 1.0 mass % or less of Fe, 1.5 mass % or less of Cu, 3.0 mass % or less of Zn, and 0.2 mass % or less of Ti, and the balance is composed of aluminum and inevitable impurities. It should be noted that, for the embodiment (A) or (C), that is, for the embodiment in which only the core material contains X atoms or the embodiment in which both the core material and the brazing material contain X atoms, the content of each X atom in the aluminum alloy of the core material is 0.01 to 2.0 mass %, preferably 0.1 to 1.8 mass %, and for the embodiment (B), that is, for the embodiment in which only the brazing material contains X atoms, the content of each X atom in the aluminum alloy of the core material is 0 mass %.

[0054] In the aluminum alloy forming the core material, Mn effectively functions for strength increase and potential adjustment. When the core material contains Mn, the Mn content in the core material is 1.8% by mass or less. If the Mn content in the core material exceeds 1.8% by mass, cracks are easily generated during material rolling. In addition, from the viewpoint of easily obtaining the effect of strength increase, the Mn content in the core material is preferably 0.3% by mass or more.

[0055] In the aluminum alloy forming the core material, Si plays a role in increasing the strength. When the core material contains Si, the Si content in the core material is 1.2% by mass or less. If the Si content in the core material exceeds 1.2% by mass, the melting point is excessively reduced, local melting occurs during brazing, the core material is deformed, and the corrosion resistance is reduced. In addition, from the viewpoint of easily obtaining the effect of increasing the strength, the Si content in the core material is preferably 0.1% by mass or more.

[0056] In the aluminum alloy forming the core material, Fe plays a role in increasing strength. When the core material contains Fe, the Fe content in the core material is 1.0 mass % or less. If the Fe content in the core material exceeds 1.0 mass %, it is easy to produce huge precipitates while the corrosion resistance is reduced. In addition, from the viewpoint of easily obtaining the effect of increasing strength, the Fe content in the core material is preferably 0.1 mass % or more.

[0057] In the aluminum alloy forming the core material, Cu plays a role in strength enhancement and potential adjustment. When the core material contains Cu, the Cu content in the core material is 1.5% by mass or less. If the Cu content in the core material exceeds 1.5% by mass, intergranular corrosion is likely to occur, and the melting point is excessively reduced. In addition, from the viewpoint of easily obtaining the effect of strength enhancement, the Cu content in the core material is preferably 0.05% by mass or more.

[0058] In the aluminum alloy forming the core material, Zn plays a role in potential adjustment. When the core material contains Zn, the Zn content in the core material is 3.0 mass% or less. If the Zn content in the core material exceeds 3.0 mass%, the natural electrode potential is excessively reduced, and the penetration life due to corrosion is shortened. In addition, from the viewpoint of easily obtaining the potential adjustment effect, the Zn content in the core material is preferably 0.1 mass% or more.

[0059] In the aluminum alloy forming the core material, Ti plays a role in causing corrosion to be carried out in layers. When the core material contains Ti, the Ti content in the core material is 0.2% by mass or less. If the Ti content in the core material exceeds 0.2% by mass, huge precipitates are easily generated, which causes obstacles in terms of rollability and corrosion resistance. In addition, from the viewpoint of easily obtaining a layered corrosion effect, the Ti content in the core material is preferably 0.06% by mass or more.

[0060] The aluminum alloy of the brazing filler metal is an aluminum alloy containing: 4.0 to 13.0 mass % Si; X atoms having a content of 0.03 mass % or less of each X atom; and 0.2 mass % or less of Bi, with the remainder being composed of aluminum and inevitable impurities. It should be noted that in the embodiment (A), that is, the embodiment in which only the core material contains X atoms, the content of each X atom in the aluminum alloy of the brazing filler metal is 0 mass %, and in the embodiment (B) or (C), that is, the embodiment in which only the brazing filler metal contains X atoms or the embodiment in which both the core material and the brazing filler metal contain X atoms, the content of each X atom in the aluminum alloy of the brazing filler metal is 0.001 to 0.03 mass %.

[0061] The brazing material contains 4.0 to 13.0 mass % of Si. If the Si content in the brazing material is less than the above range, the bonding property is deteriorated, and if it exceeds the above range, cracks are likely to occur during material production, making it difficult to produce a brazing sheet.

[0062] In the aluminum alloy forming the brazing filler metal, Fe is an inevitable impurity present in the aluminum billet, and if it is 0.8 mass % or less, it will not hinder the effect of the present invention. Although there are billets with a low Fe content, if a billet with a high purity is used, the cost will increase. In addition, if the recycling of aluminum scrap recovered from the market is taken into consideration, it is acceptable if the Fe content is 0.8 mass % or less.

[0063] In the aluminum alloy forming the brazing filler metal, Bi effectively functions to reduce the surface tension of the Al-Si molten solder. When the brazing filler metal contains Bi, the Bi content in the brazing filler metal is 0.2 mass % or less. If the Bi content in the brazing filler metal exceeds 0.2 mass %, both sides of the brazing filler metal after brazing will turn black and the brazing property will be reduced. In addition, from the viewpoint of easily obtaining the effect of reducing the surface tension, the Bi content in the brazing filler metal is preferably 0.004 mass % or more.

[0064] An oxide film is formed on the surface of the brazing material of the aluminum alloy brazing sheet of the present invention. In addition, the molar ratio of each X atom to Al in the oxide film formed on the surface of the brazing material of the aluminum alloy brazing sheet of the present invention is preferably 0.2 or less. When the molar ratio of each X atom to Al in the oxide film formed on the surface of the brazing material (X atom / Al) is within the above range, the volume change rate of the oxide containing X atoms formed by brazing heating relative to the oxide film formed on the surface of the brazing material before brazing is easily 0.99 or less. It should be noted that when the oxide film formed on the surface of the brazing material of the aluminum alloy brazing sheet of the present invention contains two or more X atoms, the molar ratio of each X atom to Al in terms of atomic conversion is 0.2 or less, which means that for any one X atom, the molar ratio of the X atom to Al in terms of atomic conversion is 0.2 or less.

[0065] The thickness of the oxide film formed on the surface of the brazing material of the aluminum alloy brazing sheet of the present invention is preferably 30 nm or less because the oxide film is easily destroyed. If the thickness of the oxide film formed on the surface of the brazing material exceeds 30 nm, it is difficult to destroy the oxide film.

[0066] The aluminum alloy brazing sheet of the present invention may also be a brazing sheet in which a brazing filler metal is coated on one side of a core material and a sacrificial anode material is coated on the other side. The sacrificial anode material is used to provide corrosion resistance to the sacrificial anode material side, and is formed of an aluminum alloy containing 0.9 to 6.0 mass % Zn, with the remainder being aluminum and inevitable impurities. If the Zn content in the aluminum alloy of the sacrificial anode material is less than the above range, the corrosion protection effect is insufficient, and if it exceeds the above range, corrosion is promoted and the corrosion penetration life is reduced.

[0067] The aluminum alloy brazing sheet of the present invention is obtained by overlapping a core material containing a predetermined additive component and a brazing filler metal, or overlapping a core material containing a predetermined additive component, a brazing filler metal, and a sacrificial anode material, forming a laminated material by hot rolling, and then processing it in a hot state to a plate thickness of about 2 to 3 mm, and then cold rolling it to a thickness of about 1 to 2 mm and a thickness of about 0.05 mm, thereby obtaining the aluminum alloy brazing sheet of the present invention. In these manufacturing processes, intermediate annealing or final annealing is performed.

[0068] Furthermore, in the manufacture of the aluminum alloy brazing sheet of the present invention, it is preferred to suppress the growth of the oxide film and the concentration of X atoms in the oxide film during the manufacturing process. That is, a preferred embodiment of the method for manufacturing the aluminum alloy brazing sheet of the present invention is a method for manufacturing an aluminum alloy brazing sheet, which is a method for manufacturing an aluminum alloy brazing sheet in which a core material and a brazing filler metal are overlapped, or a core material, a brazing filler metal and a sacrificial anode material are overlapped, and then hot and cold rolling is performed to obtain a brazing sheet, which is a method for manufacturing an aluminum alloy brazing sheet in which intermediate annealing or final annealing is performed during the manufacturing process,

[0069] The core material is formed of aluminum or an aluminum alloy, and the brazing filler metal is formed of an aluminum alloy containing 4.0 to 13.0 mass % of Si.

[0070] Either or both of the core material and the brazing filler metal contain any one or two or more of X atoms (X is Mg, Li, Be, Ca, Ce, La, Y and Zr),

[0071] When only the core material contains X atoms, the content of each X atom in the core material is 0.01 to 2.0 mass %.

[0072] When the brazing material contains only X atoms, the content of each X atom in the brazing material is 0.001 to 0.03 mass %.

[0073] When both the core material and the brazing filler metal contain X atoms, the content of each X atom in the core material is 0.01 to 2.0 mass %, and the content of each X atom in the brazing filler metal is 0.001 to 0.03 mass %,

[0074] In the intermediate annealing or final annealing performed in the manufacturing process, the intermediate annealing or final annealing is performed by heating at 250 to 450° C. in an atmosphere controlled to have an oxygen concentration of 1000 ppm or less and a dew point of −20° C. or less, and then taking out of the furnace at 250° C. or less.

[0075] In the manufacturing method of the aluminum alloy brazing sheet of the present invention, the types and contents of the added components in the core material, brazing filler metal and sacrificial anode material overlapped before hot rolling are the same as the components and contents in the core material, brazing filler metal and sacrificial anode material of the aluminum alloy brazing sheet of the present invention.

[0076] That is, the core material is formed by the following aluminum alloy, which contains: X atoms with a content of each X atom of 2.0 mass% or less; and any one or two or more of Mn of 1.8 mass% or less, preferably 0.3-1.8 mass%, Si of 1.2 mass% or less, preferably 0.1-1.2 mass%, Fe of 1.0 mass% or less, preferably 0.1-1.0 mass%, Cu of 1.5 mass% or less, preferably 0.05-1.5 mass%, Zn of 3.0 mass% or less, preferably 0.1-3.0 mass% and Ti of 0.2 mass% or less, preferably 0.06-0.2 mass%, and the balance is composed of aluminum and inevitable impurities. It should be noted that in the form in which only the core material contains X atoms or in the form in which both the core material and the brazing material contain X atoms, the content of each X atom in the aluminum alloy of the core material is 0.01 to 2.0 mass%, preferably 0.1 to 1.8 mass%. In the form in which only the brazing material contains X atoms, the content of each X atom in the aluminum alloy of the core material is 0 mass%.

[0077] The brazing filler metal is formed of an aluminum alloy containing 4.0 to 13.0 mass % of Si, and X atoms each containing 0.03 mass % or less of X atoms, and containing 0.2 mass % or less of Bi as required, preferably 0.004 to 0.2 mass %, and the balance consisting of aluminum and inevitable impurities. It should be noted that in the case where only the core material contains X atoms, the content of each X atom in the aluminum alloy of the brazing filler metal is 0 mass %, and in the case where only the brazing filler metal contains X atoms or both the core material and the brazing filler metal contain X atoms, the content of each X atom in the aluminum alloy of the brazing filler metal is 0.001 to 0.03 mass %, preferably 0.005 to 0.025 mass %.

[0078] In the method for manufacturing the aluminum alloy brazing sheet of the present invention, a core material and a brazing filler metal are overlapped, or a core material, a brazing filler metal and a sacrificial anode material are overlapped, and then hot rolling and cold rolling are performed. In the hot rolling, a laminate is formed at 400 to 550° C., and then processed to a plate thickness of 2 to 3 mm in a hot state. In the cold rolling, the sheet is rolled multiple times in a cold manner to a predetermined thickness of the aluminum alloy brazing sheet.

[0079] In the method for producing the aluminum alloy brazing sheet of the present invention, intermediate annealing or final annealing is performed between cold rolling or after the final cold rolling.

[0080] Furthermore, in the manufacturing method of the aluminum alloy brazing sheet of the present invention, in the intermediate annealing or the final annealing, the intermediate annealing or the final annealing is performed by heating at 250 to 450°C in an atmosphere managed to have an oxygen concentration of 1000 ppm or less and a dew point of -20°C or less, and then the sheet is taken out of the furnace at a temperature below 250°C. Since the intermediate annealing or the final annealing is a high-temperature process, it has a great influence on the state of the oxide film. The atmosphere of the intermediate annealing or the final annealing is an inert gas atmosphere such as nitrogen and argon. By performing the intermediate annealing or the final annealing in an atmosphere managed to have an oxygen concentration of 1000 ppm or less and a dew point of -20°C or less, and then taking the sheet out of the furnace at a temperature below 250°C, it is easy to obtain a brazing sheet having oxide particles containing X atoms formed on the surface with a volume change rate of 0.99 or less relative to the oxide film before the brazing heating by brazing heating. If the oxygen concentration in the atmosphere during the intermediate annealing or the final annealing exceeds 1000ppm, the growth of the oxide film is promoted, or the concentration of X atoms in the oxide film is likely to increase. In addition, if the dew point of the atmosphere during the intermediate annealing or the final annealing exceeds -20°C, a hydroxide film is likely to be formed, and the oxide film is likely to thicken. In addition, if the furnace temperature exceeds 250°C, it is easy to react with oxygen or moisture in the atmosphere on the surface of the material. The annealing time during the intermediate annealing or the final annealing is preferably more than 1 hour.

[0081] The aluminum alloy brazing sheet of the present invention is used for brazing in an inert gas atmosphere without using a flux. The brazing temperature in the brazing is 580 to 615°C.

[0082] The aluminum alloy brazing sheet of the present invention is brazed in an inert gas atmosphere without using a flux, and oxide particles containing X atoms having a volume change rate of 0.99 or less relative to the oxide film before brazing heating are formed on the surface. Therefore, the newly formed surface of the brazing material is easily exposed, and excellent brazing properties are exhibited.

[0083] The aluminum alloy sheet (A) of the present invention is an aluminum alloy sheet obtained by brazing and heating the aluminum alloy brazing sheet of the present invention at 580 to 615°C in an inert gas atmosphere without using a flux, and is an aluminum alloy sheet having oxide particles containing X atoms formed on the surface of the aluminum alloy sheet, the volume change rate of which is 0.99 or less relative to the oxide film of the aluminum alloy brazing sheet before brazing heating. The oxide containing X atoms formed on the surface of the aluminum alloy sheet (A) of the present invention is granular, and the volume change rate of which is 0.99 or less relative to the oxide film of the aluminum alloy brazing sheet before brazing heating, so a new surface of the aluminum alloy appears on a part of the surface. The inert gas is nitrogen, argon, etc. The oxygen concentration of the atmosphere is 1 to 100 ppm, preferably 1 to 50 ppm, and the dew point is below -20°C, preferably below -40°C.

[0084] The aluminum alloy sheet (A) of the present invention is an aluminum alloy sheet after the aluminum alloy brazing sheet is brazed.

[0085] The heat exchanger of the present invention is characterized in that it is a heat exchanger obtained by using the aluminum alloy brazing sheet of the present invention and performing brazing heating in an inert gas atmosphere without using a flux.

[0086] In the heat exchanger, oxide particles containing X atoms having a volume change rate of 0.99 or less relative to that of the oxide film of the aluminum alloy brazing sheet before brazing heating are formed on the surface of the aluminum alloy sheet after brazing heating.

[0087] The heat exchanger of the present invention is a heat exchanger obtained by using the aluminum alloy sheet of the present invention as an aluminum alloy brazing sheet for manufacturing a heat exchanger, that is, forming the aluminum alloy sheet of the present invention into the shape of a component using the brazing sheet in a heat exchanger, assembling the aluminum alloy brazing sheet of the present invention and other components to be brazed, and brazing and heating in an inert gas atmosphere. The brazing temperature is 580 to 615°C, and the inert gas is nitrogen, argon, etc. The oxygen concentration of the atmosphere is 1 to 100 ppm, preferably 1 to 50 ppm, and the dew point is below -20°C, preferably below -40°C. As other components brazed together with the aluminum alloy brazing sheet of the present invention, tubes, headers, fins, inlet and outlet piping, etc. can be listed.

[0088] In the heat exchanger of the present invention, after the aluminum alloy brazing sheet is brazed and heated (aluminum alloy sheet (A)), oxide particles containing X atoms are formed on the surface of the aluminum alloy sheet having a volume change rate of less than 0.99 relative to the oxide film of the aluminum alloy brazing sheet before brazing heating (aluminum alloy brazing sheet of the present invention).

[0089] Example

[0090] The following examples of the present invention are compared with comparative examples to demonstrate the effects of the present invention. It should be noted that these examples illustrate one embodiment of the present invention, and the present invention is not limited to them.

[0091] The brazing filler metal, sacrificial anode material and core material having the composition shown in Table 1 and Table 2 were respectively cast into ingots by continuous casting. For the core material, the end face of the obtained ingot was cut to a length of 163 mm and a width of 163 mm, the end face of the core material with only the brazing filler metal cladding was cut to a thickness of 27 mm, and the end face of the core material with the cladding brazing filler metal and the sacrificial anode material was cut to a thickness of 25.5 mm. For the brazing filler metal, the obtained ingot was hot-rolled at 500°C to a thickness of 3 mm, and after cooling, it was cut into a length of 163 mm and a width of 163 mm. For the sacrificial anode material, the obtained ingot was hot-rolled at 500°C to a thickness of 3 mm, then cold-rolled to 1.5 mm, and cut into a length of 163 mm and a width of 163 mm.

[0092] [Table 1]

[0093]

[0094] [Table 2]

[0095]

[0096] For the material of cladding solder only, the prepared solder and core material were overlapped, hot rolled and cold rolled to a thickness of 0.4 mm, and finally annealed under the conditions shown in Table 3 to obtain a soft cladding plate. For the material of cladding solder and sacrificial anode material, the prepared solder, core material and sacrificial anode material were overlapped, hot rolled and cold rolled to a thickness of 0.4 mm, and finally annealed under the conditions shown in Table 4 to obtain a soft cladding plate. The obtained cladding plate was used as a test material.

[0097] The thickness of the oxide film of the test material was measured by GD-OES (glow discharge emission spectrometry). By GD-OES, the material surface was analyzed in the depth direction, and the position of the half-peak width of the measured oxygen element was defined as the oxide film thickness. In addition, the atomic conversion molar ratio of each X atom in the oxide film relative to aluminum (X atom / Al) was also analyzed by GD-OES.

[0098] The test material was pressed into a cup shape, degreased with acetone, and assembled into Figure 1 The cupping test piece shown. Fins formed and degreased from a 0.1 mm thick 3003 alloy sheet are placed inside the cupping test piece, and brazing heating is performed in a nitrogen furnace without using a flux, and brazing is performed. The nitrogen furnace is a two-chamber experimental furnace, and the oxygen concentration during heating is 100 ppm and the dew point is -20°C. The oxygen concentration during brazing is 10 to 15 ppm and the dew point is -40°C. The temperature reached by the test pieces is 600°C.

[0099] For the outside, the weld leg formed on the outside of the flare joint was visually evaluated in five levels: A: a weld leg of uniform size was continuously formed; B: a state where the weld leg size varied, but there was no weld leg discontinuity when more than 80% of the uniform weld leg was formed; C: a state where the weld leg size varied, but there was no weld leg discontinuity when more than 40% of the uniform weld leg was formed; D: a state where the weld leg was partially discontinuous and discontinuous or a state where the weld leg size was less than 40%; E: a state where there was almost no weld leg formed or no joint. Among them, A to C were judged as acceptable levels. For the inside, the brazed test piece was divided into two parts, and the weld leg formation state was visually evaluated in five levels in the same way as above, with the inner side of the flare joint and the joint of the fin as the object.

[0100] The volume change rate of the oxide particles containing X atoms formed after brazing relative to the oxide film before brazing heating is calculated as follows: First, the crystal structure of the oxide particles containing X atoms formed is determined by thin film X-ray diffraction. Next, the molecular weight of the oxide is divided by the density recorded in the known literature to calculate the volume of each oxygen atom, and the volume is divided by the volume of each oxygen atom of the oxide film before brazing heating to calculate the above volume change rate. In thin film X-ray diffraction, the measurement is performed at an incident angle of 1°. The volume of each oxygen atom of the oxide film before brazing heating is set to Al2O3 and its density is set to 3.0 g / cm 3 Come and ask for it.

[0101] [Table 3]

[0102]

[0103] (Example)

[0104] The clad plates of the combination of brazing filler metal, core material and sacrificial anode material shown in Table 4 were prepared, and the obtained clad plates were analyzed and tested for brazing properties. The results are shown in Table 4. In addition, the SEM photograph (30000 times) of the surface of Test No. 30 is shown in Table 4. Figure 2 In this SEM photograph, particles that appear as white spots are oxide particles containing X atoms, and flat surfaces that appear black are newly formed surfaces generated on the surface of the brazing material during brazing heating.

[0105] (Comparative Example)

[0106] Cladding plates having the combinations of brazing filler metals, core materials, and sacrificial anode materials shown in Table 5 were prepared, and the obtained cladding plates were analyzed and tested for brazing properties.

[0107] It should be noted that, since the Si content of the brazing material of test material 34 was high, cracks occurred during the rolling of the material, and therefore, analysis and performance tests could not be performed. In test pieces 39 and 40, the surface of the brazing material after brazing turned black. In test material 42, corrosion by the molten brazing material and deformation of the test material after brazing were observed. Since the Zn content of the sacrificial anode material of test material 43 was high, cracks occurred during the rolling of the material, and therefore, analysis and performance tests could not be performed.

[0108] [Table 4]

[0109]

[0110] [Table 5]

[0111]

Claims

1. A method for manufacturing an aluminum alloy brazing sheet, characterized in that: The present invention relates to a method for manufacturing an aluminum alloy brazing sheet, in which a core material and a brazing filler metal are overlapped, or a core material, a brazing filler metal and a sacrificial anode material are overlapped, and then hot and cold rolling is performed to obtain a brazing sheet. The present invention relates to a method for manufacturing an aluminum alloy brazing sheet, in which intermediate annealing or final annealing is performed in the manufacturing process. The core material is formed of aluminum or an aluminum alloy, and the brazing filler metal is formed of an aluminum alloy containing 4.0 to 13.0 mass % of Si. Either or both of the core material and the brazing filler metal contain any one or two or more of the X atoms, wherein X is Mg, Li, Be, Ca, Ce, La, Y, and Zr. When only the core material contains X atoms, the content of each X atom in the core material is 0.01 to 2.0 mass %. When the brazing material contains only X atoms, the content of each X atom in the brazing material is 0.001 to 0.03 mass %. When both the core material and the brazing filler metal contain X atoms, the content of each X atom in the core material is 0.01 to 2.0 mass %, and the content of each X atom in the brazing filler metal is 0.001 to 0.03 mass %, In the intermediate annealing or final annealing performed in the manufacturing process, the intermediate annealing or final annealing is performed by heating at 250 to 450°C in an atmosphere controlled to have an oxygen concentration of 1000 ppm or less and a dew point of -20°C or less, and then taking out of the furnace at 250°C or less. By brazing heating in an inert gas atmosphere without using a flux, oxide particles containing X atoms having a volume change rate of 0.99 or less relative to the oxide film before brazing heating are formed on the surface. The molar ratio of each X atom to Al atom in an oxide film formed on the surface of the aluminum alloy brazing sheet is 0.2 or less.

2. The method for manufacturing an aluminum alloy brazing sheet according to claim 1, characterized in that: The thickness of the oxide film formed on the surface of the aluminum alloy brazing sheet is 30 nm or less.

3. The method for manufacturing an aluminum alloy brazing sheet according to claim 1 or 2, characterized in that: The core material is the following aluminum alloy, and the aluminum alloy contains: The content of each X atom is 2.0 mass % or less of X atoms; and any one or two or more of 1.8 mass % or less of Mn, 1.2 mass % or less of Si, 1.0 mass % or less of Fe, 1.5 mass % or less of Cu, 3.0 mass % or less of Zn and 0.2 mass % or less of Ti, The balance consists of aluminum and unavoidable impurities.

4. The method for manufacturing an aluminum alloy brazing sheet according to claim 1 or 2, characterized in that: The brazing filler metal is an aluminum alloy as follows, wherein the aluminum alloy contains: 4.0 to 13.0 mass % Si; and The content of each X atom is 0.03 mass % or less of X atoms, The balance consists of aluminum and unavoidable impurities.

5. The method for manufacturing an aluminum alloy brazing sheet according to claim 3, characterized in that: The brazing filler metal is an aluminum alloy as follows, wherein the aluminum alloy contains: 4.0 to 13.0 mass % Si; and The content of each X atom is 0.03 mass % or less of X atoms, The balance consists of aluminum and unavoidable impurities.

6. The method for manufacturing an aluminum alloy brazing sheet according to claim 1 or 2, characterized in that: The brazing filler metal is an aluminum alloy further containing 0.004 to 0.2 mass % of Bi.

7. The method for manufacturing an aluminum alloy brazing sheet according to claim 3, characterized in that: The brazing filler metal is an aluminum alloy further containing 0.004 to 0.2 mass % of Bi.

8. The method for manufacturing an aluminum alloy brazing sheet according to claim 4, characterized in that: The brazing filler metal is an aluminum alloy further containing 0.004 to 0.2 mass % of Bi.

9. The method for manufacturing an aluminum alloy brazing sheet according to claim 5, characterized in that: The brazing filler metal is an aluminum alloy further containing 0.004 to 0.2 mass % of Bi.

10. The method for manufacturing an aluminum alloy brazing sheet according to claim 1 or 2, characterized in that: The brazing filler metal is coated on one side, and a sacrificial anode material of an aluminum alloy containing 0.9 to 6.0 mass % of Zn and the balance of aluminum and inevitable impurities is coated on the other side. The inert gas atmosphere has an oxygen concentration of 1 to 100 ppm and a dew point of -20°C or less.

11. The method for manufacturing an aluminum alloy brazing sheet according to claim 3, characterized in that: The brazing filler metal is coated on one side, and a sacrificial anode material of an aluminum alloy containing 0.9 to 6.0 mass % of Zn and the balance of aluminum and inevitable impurities is coated on the other side. The inert gas atmosphere has an oxygen concentration of 1 to 100 ppm and a dew point of -20°C or less.

12. The method for manufacturing an aluminum alloy brazing sheet according to claim 4, characterized in that: The brazing filler metal is coated on one side, and a sacrificial anode material of an aluminum alloy containing 0.9 to 6.0 mass % of Zn and the balance of aluminum and inevitable impurities is coated on the other side. The inert gas atmosphere has an oxygen concentration of 1 to 100 ppm and a dew point of -20°C or less.

13. The method for manufacturing an aluminum alloy brazing sheet according to claim 5, characterized in that: The brazing filler metal is coated on one side, and a sacrificial anode material of an aluminum alloy containing 0.9 to 6.0 mass % of Zn and the balance of aluminum and inevitable impurities is coated on the other side. The inert gas atmosphere has an oxygen concentration of 1 to 100 ppm and a dew point of -20°C or less.

14. The method for manufacturing an aluminum alloy brazing sheet according to claim 6, characterized in that: The brazing filler metal is coated on one side, and a sacrificial anode material of an aluminum alloy containing 0.9 to 6.0 mass % of Zn and the balance of aluminum and inevitable impurities is coated on the other side. The inert gas atmosphere has an oxygen concentration of 1 to 100 ppm and a dew point of -20°C or less.

15. The method for producing an aluminum alloy brazing sheet according to any one of claims 7 to 9, characterized in that: The brazing filler metal is coated on one side, and a sacrificial anode material of an aluminum alloy containing 0.9 to 6.0 mass % of Zn and the balance of aluminum and inevitable impurities is coated on the other side. The inert gas atmosphere has an oxygen concentration of 1 to 100 ppm and a dew point of -20°C or less.

Citation Information

Patent Citations

  • Production of non-oxidation gas atmosphere fluxless brazing material and brazing method

    JP1999285817A

  • Method for brazing aluminum material

    JP2004358519A

  • Flux-less brazing method of aluminum material, brazing sheet for flux-less brazing and method for manufacturing the same, brazing structure

    JP2013215797A

  • Fluxless brazing method for aluminum material and method of manufacturing brazed structure

    JP2013220436A

  • Aluminum alloy brazing sheet

    JP2013233552A